Alienation of Students’ Voices in Indonesia - Yusuf, Raidah Intizar; Cangara, Hafied (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This research aims to examine the influence of government priorities, oligarchic interests, and other factors that may hinder the translation of activism into concrete policy changes within the framework of alienation. The study employs a qualitative approach utilizing an unobtrusive data collection method, explicitly focusing on documentary analysis through news reports and related academic literature. The findings suggest a collective expression of discontent through social movements led by Indonesian student activists, encompassing various aspects of their lives. However, student voices are repeatedly silenced. One of the constraints is the need for more partnership between activists and the media, resulting from media conglomeration. In addition to media conglomeration, the regime's prioritization of economic development has relegated student voices to mere echoes, demonstrating that alienation occurs from multiple directions.